(untitled) (Journal of Nematode Morphology and Systematics, 2012)
The three species previously in the genus Radopholoides (R. litoralis, R. laevis and R. triversus) had been transferred to the genus Hoplotylus, and Radopholoides has recently been synonymised to Hoplotylus, comprising a total of seven described valid species presently in this genus. The four species originally in Hoplotylus are shown to be differentiated from the three species previously in Radopholoides by their oblique lip region in males, subterminal bursa, short gubernaculum, shape of the stylet knobs in females and other morphological characteristics. The synonymisations are considered as not justifi ed, the genus Radopholoides is restored and the three species retained under this genus. Studies on numerous H. femina specimens from Germany and of three H. sjacobi populations recently collected in New Zealand contributed to these conclusions; new morphological details supplementing previous descriptions are given. While both species are clearly distinguished by the shape of stylet knobs, tail and other characters, the distinction of H. silvaticus and H. montanus appears less evident. Their identity should be checked by molecular studies.